Optimal location and sizing of DG and D-STATCOM in distribution networks - Surender Reddy Salkuti (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The main aim of this paper is to determine optimal locations and sizing of Distributed Generations (DGs) and Distribution STATic COMpensator (D-STATCOM) in the distribution network for reducing the system losses and to improve the voltage profile. In this paper, the loss sensitivity factor approach is used to determine optimal location for DG and voltage stability index is used to determine optimal location for D-STATCOM. The objective of proposed optimization problem is to minimize the total real power losses in the system while satisfying several equality and inequality constraints. Artificial fish swarm optimization algorithm (AFSOA) is used to determine the optimal size of DG and D-STATCOM. The simulations are performed on standard 33 bus and 69 bus radial distribution systems and the obtained  results show the feasibility and effectiveness of proposed approach.